Life-threatening hypernatremia in a 22-year-old man with concurrent diabetic ketoacidosis and hyperosmolar hyperglycemic state (Indian Journal of Case Reports, 2020)
In diabetic ketoacidosis (DKA), hyponatremia is commonly observed due to hyperglycemia-induced water shift and osmotic diuresis. Thus, hypernatremia is rare and indicative of severe free water loss. We describe here a case of DKA with life-threatening hypernatremia. A 22-year-old type 1 diabetic male was admitted after experiencing polyuria and polydipsia, followed by nausea, vomiting, and lethargy for 2 weeks. On admission, plasma glucose was 1230 mg/dL and plasma sodium was 158 mEq/L. The patient developed acute kidney injury, lactic acidosis, and ketosis. Despite fluid resuscitation, sodium level continued to rise to 180 mEq/L. Tachycardia persisted and shock liver developed. After free water-deficit calculation, the patient was given more boluses of isotonic fluid in addition to 0.45% NaCl. Tachycardia began to improve, and hypernatremia and hyperglycemia were safely reduced. This case demonstrated how tedious volume evaluation and resuscitation helped the patient fully recover despite extreme hypernatremia, lethargy, and multiorgan failure.